The Effects of Vitamin-Mineral Supplements on Serious Rule Violations in Correctional Facilities for Young Adult Male Inmates: A Randomized Controlled Trial - Schoenthaler, Stephen (Crime & delinquency, 2023)
We investigated whether vitamin-mineral supplementation could reduce serious rule violations. In this randomized, controlled, double-blind trial, young adult male inmates were included. For 15?weeks, they received a daily dose with vitamin-mineral supplements of approximately 100% Recommended Dietary Allowance (RDA) (n?=?149), or a higher-dose formula (n?=?150), or placebo (n?=?150). Serious rule violations were the primary outcome. In the lower-dose group there were 39% fewer rule violations than in the placebo group (relative risk?=?.61; 95% confidence interval [CI]:.41?.90, p?=?.01). In the higher-dose group the difference did not reach statistical significance. About 100% RDA, but not higher doses supplements, resulted in less serious rule violations than placebo.